Systemic Hypoxia and Interventions on Nitric Oxide Metabolism Affect Retinal Vasomotion in Healthy Subjects - Petersen, Line; Bek, Toke (Investigative ophthalmology & visual science, 2024)
Previous in vitro studies on porcine retinal arterioles have shown that the frequency and amplitude of retinal vasomotion can be affected by hypoxia and nitric oxide (NO). However, it is unknown whether these effects can be reproduced in humans in vivo. Video recordings of retinal arterioles from 40 healthy subjects were studied before and during breathing of a hypoxic gas mixture consisting of 12.5% oxygen and 87.5% nitrogen. The experiments were repeated before and after the addition of either an NO donor or continuous infusion of an NO synthesis inhibitor. The harmonic content of spontaneous diameter changes in retinal arterioles was extracted by Fourier analysis, and the effects of the interventions were studied on the amplitudes of diameter oscillations in the frequency bands 1: 0.5/min-3.5/min, 2: 4/min-7.5/min, 3: 8/min-17.5/min, and 4: 18/min-30/min. Hypoxia significantly increased the amplitude of spontaneous diameter oscillations within the low (1) and high (3-4) frequency bands (P < 0.006 for all comparisons), and the effect in frequency band 1 was eliminated by the NO donor. In frequency band 2, hypoxia had no significant effect on the amplitude of diameter oscillations, but the amplitudes were significantly reduced by the NO donor (P < 0.01) and significantly increased by the NO synthesis inhibitor (P = 0.03). Hypoxia and interventions on NO metabolism can affect spontaneous diameter oscillations in retinal arterioles. Disturbances in vasomotion may play a role in hemodynamic changes in retinal diseases in which hypoxia and changes in NO metabolism are involved in the disease pathogenesis.